Pengaruh Komunikasi Interpersonal Terhadap Prestasi Kerja Karyawan Dengan Lingkungan Kerja Sebagai Variabel Intervening Pada CV. Tugu Chocolate Yogyakarta - Anjas Asmara (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to describe 1) the influence of interpersonal communication on employee performance, 2) the influence of work environment on employee performance, 3) the influence of interpersonal communication to the work environment, 4) The influence of interpersonal communication on employee performance with work environment as variable intervening on CV. Tugu Chocolate Yogyakarta. Variables in this research are interpersonal communication, work environment, and employee achievement. The population in this study is all employees in CV. Yogyakarta Chocolate Monument, amounting to 96 people and only 49 people who sampled the study. Data collection method used questionnaire method, while data analysis technique using simple linear regression analysis and multiple linear regression analysis supported by T (T-Test) and F (F-Test) test and classical assumption test consisting of test normality, multicolinearity test, and heteroscedasticity test. The results showed that there is a positive and significant influence of interpersonal communication on employee performance CV. Yogyakarta Chocolate Monument by 0.000 (p < 0.05). There is a positive and insignificant effect of work environment on employee performance CV. The Yogyakarta Chocolate Monument is 0.241 (p > 0.05). There is a positive and significant influence of interpersonal communication to the work environment of CV employees. Yogyakarta Chocolate Monument by 0,021 (p < 0,05). So there is influence between interpersonal communication on employee performance with work environment as intervening variable.